Identification of autophagy-related immune targets for enhancing immunotherapy in pancreatic cancer aggressiveness - Deng, Qianxi; Wu, Linju; He, Jin; Wu, Fan; Jiang, Zheng (Discover. Oncology, 2025)
Background Pancreatic cancer (PC) presents significant challenges in oncology, with metastasis critically affecting patient outcomes. Autophagy-related genes (ARGs)’s involvement in influencing immune activity and metastasis in PC remains inadequately understood. Aim This study seeks to identify and validate five ARGs that could serve as immune targets, enhancing enhancing Pancreatic cancer metastasis (PCM)’s prognostic models and informing immunotherapy strategies. Methods ARGs that were diffentially expressed were screened, followed by Cox regression and LASSO analyses to pinpoint five genes linked to overall survival (OS). A prognostic model was developed and validated using ROC curves. Functional analyses, including GO and KEGG, were performed to elucidate ARG mechanisms. Immune infiltration and TFs/microRNA/mRNA networks were assessed to understand ARG-immune cell interactions. Experimental validation employed real-time PCR, IHC, and Western blotting, supported by TCGA data. Functional assays explored RHEB’s role in PC, particularly its interaction with LC3. Results Five ARGs (CASP1, RHEB, CHMP2B, MYC, and HDAC6) were identified, contributing to a robust prognostic model where low-risk individuals showed significantly longer OS. The model demonstrated high AUC scores, indicating strong prognostic capability. CD8 T cells and Treg cells’ elevated levels were observed in metastatic subjects. RHEB knockdown suppressed cancer cell proliferation and invasion, with a negative correlation between RHEB and LC3, suggesting a role in autophagy-mediated modulation of PC metastasis. Conclusion This study introduces a novel prognostic model incorporating five ARGs, highlighting their potential as immune targets for cancer immunotherapy. The negative correlation between RHEB and LC3 suggests a therapeutic pathway for PCM intervention, laying the groundwork for more effective anti-cancer strategies. These findings advance the identification of novel immune targets and signaling pathways, aligning with precision medicine goals in cancer treatment.